WIOD SAMs adjusted with Eurostat data for the EU-27. Issue 4 (2nd October 2018) - Álvarez-Martínez, María T.; López-Cobo, Montserrat
ABSTRACT: This paper provides a new set of Social Accounting Matrices (SAMs) for the EU-27 and describes their construction process. The World Input–Output Database (WIOD) has been used as the main data source, and it has been completed with information from National Accounts in Eurostat. The SAMs include a disaggregation of labour by skills and the disaggregation of the foreign sector into the EU and Rest of the world. It is described how to elaborate a symmetric Input–Output table product by product at purchasers' prices using supply and use tables and applying the industry technology. It is also described the reallocation of social contributions needed to properly assign tax revenues to government and avoid the usually overlooked problems generated by the second redistribution of income. The description of the SAMs and their availability for the EU-27 can be very useful to researchers in applied economics using CGE and SAM models.